2022
DOI: 10.3389/fvets.2022.904886
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester (CAPE) Improves Boar Sperm Quality and Antioxidant Capacity in Liquid Preservation (17°C) Linked to AMPK Activity Maintenance

Abstract: Liquid preservation of boar sperm is crucial for artificial insemination application in pig production. However, time-dependent oxidative damage to sperm is one of the major challenges during the liquid preservation period. Caffeic acid phenethyl ester (CAPE) possesses excellent antioxidant properties and has potential therapeutic use in reproductive organ injury linked to oxidative stress. Adenosine monophosphate (AMP)-activated protein kinase (AMPK) involves in modulating the cellular redox state and exerts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…CAPE, one of the main bioactive components of propolis, has been reported to effectively repress tumor migration [ 45 ], relieve inflammatory responses [ 46 ], inhibit oxidation, and protect neurons from apoptosis [ 28 , 47 ]. Although there have been many studies of the pharmacological effects of CAPE, there are few reports of its anti-inflammatory and anti-oxidative stress effects after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…CAPE, one of the main bioactive components of propolis, has been reported to effectively repress tumor migration [ 45 ], relieve inflammatory responses [ 46 ], inhibit oxidation, and protect neurons from apoptosis [ 28 , 47 ]. Although there have been many studies of the pharmacological effects of CAPE, there are few reports of its anti-inflammatory and anti-oxidative stress effects after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the detrimental effects of OS on semen storage, various antioxidants were added into the semen extender, and their protective effect on sperm quality was observed [ 11 , 33 , 34 ]. Furthermore, our previous investigation demonstrated that antioxidants in seminal plasma are directly involved in cryotolerance of boar spermatozoa by playing against OS induced by the freezing and thawing process [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…After four days of storage, the sperm AMPK was significantly activated. The increase in sperm SOD-like activity after four days of storage may be due to the activation of the sperm AMPK, which is suggested to promote the antioxidants in boar spermatozoa [ 33 ]. SOD scavenges O 2-• [ 12 ], and its supplementation into freezing medium was demonstrated to be beneficial to the cryosurvival of Black Bengal buck spermatozoa [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS can damage sperm mitochondria, alter MMP, induce mitochondrial dysfunction, and further affect sperm energy metabolism [ 28 ]. During sperm preservation, the AMPK signaling pathway can significantly improve sperm preservation quality and antioxidant capacity [ 29 ]. After AMPK is activated, it regulates a series of energy metabolism pathways, such as glycolysis, lipid homeostasis, and mitochondrial homeostasis, by phosphorylating key proteins [ 16 ].…”
Section: Discussionmentioning
confidence: 99%